A PEOPLE'S HISTORY OF MALAYSIA : With Emphasis on the Development of Nationalism - Syed Husin Ali (Pusat Sejarah Rakyat Berhad, 2024)
This book aims to provide a brief overview of the History of the People of Malaysia (formerly known as Malaya). The approach taken in this book differs from what is typically found in the form of Official History. The writing style in this work is more accessible and less academic, making it readable to the general public, regardless of age. The field of Malaysian history is extensive, and it is impossible to cover every aspect in a concise book like this. Therefore, the author places emphasis on a particular aspect: the development of nationalism. It can be argued that the development of nationalism is the most significant aspect of Malaysian history, as it encompasses the phase of the formation of our nation-state, which has undergone numerous waves of change.